Penerapan Teknik Role-Playing untuk Meningkatkan Disiplin Belajar Siswa SMP - Arjanto, Paul; Somae, Felix Febry (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2020)
This study aims to determine the effectiveness of role playing in improving student learning discipline. The research design was one group pretest - posttest design. Role playing interventions were held 4 times. The population in this study amounted to 339 people. Fromthis population identified as having low learning discipline from the results of the learning discipline questionnaire, then separated and devoted to being given intervention with role playing. The sample in this study amounted to 35 subjects who were identified as havinglearning discipline with a low category with a value, 6 students in the experimental group showed an average of 141.5 and 6 students in the control group showed an average of 144, 2. Role playing techniques were effective to improve Junior high school student learningdiscipline. This is based on testing the hypothesis that the results of the paired 't' test show that the average difference in student learning discipline before the role playing intervention and after the role playing intervention is 5.77143, meaning that there is an increase in learning discipline after the role playing intervention with an average of 5.77143. 5.77. the result of the calculation of the value "t" is 6,086 with Sig. .000. it means that the application of role playing is effective to improve student learning discipline.